Rosemary oil low energy nanoemulsion: optimization, µrheology, in silico, in vitro, and ex vivo characterization. Issue 15 (13th October 2022) - Vasdev, Nupur; Handa, Mayank; Kesharwani, Prashant; Shukla, Rahul
Abstract: Acetylcholine imbalance in the human brain causes dementia-related symptoms of Alzheimer's disease. Acetylcholinesterase (AChE) inhibitors prevent the lysis of acetylcholine in the brain and prevent dementia. Therefore, the present study aims to investigate the in silico and in vitro AChE potential of rosemary oil and then formulate it into nanoemulsion as an adjuvant with co-administration of Donepezil (Dz) with a thought for futuristic target for Alzheimer's diseases via the intranasal route. The aim for preparing this formulation was to add the AChE inhibition effect of the rosemary oil to the effect that acts as an additive effect along with Dz. The docking score of rosemary oil components on human cholinesterase 1GQR protein was found to be >–5 kcal/mol. In vitro AChE activity of rosemary oil confirms the prominent IC50 of oil at 0.001 µL/min. Nanoemulsion was prepared by low energy emulsification technique using Tween 80 as surfactant and ethanol or diethylene glycol monoethyl ether as cosurfactant. Droplet size, polydisperity index, and zeta potential of stable nanoemulsion was ∼16 nm, 0.1, and –6.05 mV for stable batch. High-resolution transmission electron microscopy microscopic studies depicted the spherical shape of the droplet. Micro rheology investigation of nanoemulsion clearly attributes to gel–sol–gel behaviour of formulated nanoemulsion. Thermal evaluation of nanoemulsion depicts the phase transition behaviour of ethanol-based nanoemulsion at 60 °C. Ex vivo nasal ciliotoxicity and permeation studies of formulation establish the safety of ethanol-based rosemary oil-loaded nanoemulsion and permeation mechanism of Dz from the nanoemulsion. In vitro permeation studies showed more drug penetration from the nanoemulsion as compared to the plain drug. The prepared nanoemulsion was found to be stable for 3 months at 4, 25, and 45 °C of storage. This low energy preparation method can be advantageous for the preparation of scalable nanoemulsion and can be a futuristic therapeutic for Alzheimer's disease. Abstract : UF0001